ARKAS DIGITAL TRANSFORMATION, PUBLIC ACCOUNTABILITY, AND HUMAN RESOURCE CAPACITY FOR THE EFFECTIVENESS OF BOSP FUNDS - Diyan Ika Suprapti; septiana munggarani; Dede Ginanjar; Lely Halimah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Digital transformation in the management of education funds is a strategic priority for the Indonesian government to increase the effectiveness of the 2026 Education Unit Operational Assistance Fund (BOSP). The implementation of the School Activity Plan and Budget Application (ARKAS) strengthens administrative efficiency, transparency of financial statements, and public accountability. This study uses a quantitative approach with an explanatory research design, supported by systematic literature studies from national journals Sinta 1–3 and international journals for the period 2020–2026. The results of the study show that ARKAS' digital transformation, public accountability, and human resource capacity have a significant effect on the effectiveness of the management of the BOSP Fund, strengthening transparency, community participation, and equitable access to quality education. This research confirms that the success of education digitalization does not only depend on technology, but also on transparent public governance and competent human resources.